2021
DOI: 10.1021/acs.jmedchem.1c00985
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cdc2-like Kinase 2 Inhibitors: Achievements and Future Directions

Abstract: Cdc2-like kinases (CLKs; CLK1–4) are associated with various neurodegenerative disorders, metabolic regulation, and viral infection and have been recognized as potential drug targets. Human CLK2 has received increasing attention as a regulator that phosphorylates serine- and arginine-rich (SR) proteins and subsequently modulates the alternative splicing of precursor mRNA (pre-mRNA), which is an attractive target for degenerative disease and cancer. Numerous CLK2 inhibitors have been identified, with several mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 120 publications
1
24
0
Order By: Relevance
“…Tol, known as tolerance, is the radius of the pharmacophoric feature sphere. S(disp/tol) 2 is the summation of (disp/tol) 2 values for all pharmacophoric features that successfully map corresponding chemical functionalities in the tted compound. [10][11][12][13][14][15][16][17][18][19][20]42,43 Additional 166 physicochemical descriptors that included numerous physicochemical, topological and ngerprint descriptors 55,56 were also calculated employing the "Calculate Molecular Properties" protocol implemented within Discovery Studio (version 4.5, BIOVIA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tol, known as tolerance, is the radius of the pharmacophoric feature sphere. S(disp/tol) 2 is the summation of (disp/tol) 2 values for all pharmacophoric features that successfully map corresponding chemical functionalities in the tted compound. [10][11][12][13][14][15][16][17][18][19][20]42,43 Additional 166 physicochemical descriptors that included numerous physicochemical, topological and ngerprint descriptors 55,56 were also calculated employing the "Calculate Molecular Properties" protocol implemented within Discovery Studio (version 4.5, BIOVIA, USA).…”
Section: Methodsmentioning
confidence: 99%
“… 1 Cyclin dependent-like family kinases (Cdc2-like protein kinases) are dual specific kinases that have been shown to regulate mRNA splicing by phosphorylation of serine and arginine rich proteins. 2 The Cdc2-like kinases family (CLK) consists of four isoforms CLK1–4 exhibiting the typical protein kinase folds and possessing different lengths of amino acids and they are involved in alternative splicing and RNA processing in Duchenne muscular dystrophy, Alzheimer's disease, HIV-1, influenza virus and cancer. 3 CLK4 inhibition has recently raised interest as a potential treatment for different CLK4-over expressing cancer types, i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 93 CLK2 is closely associated with many neurodegenerative diseases, metabolic diseases, and viral infection‐related diseases, and is considered as a potential drug target for these diseases. 94 Its specific inhibitory drugs are used in the experimental treatment of Alzheimer's disease, insulin resistance, and neoplasms, especially leukemia and triple‐negative breast cancer. 95 , 96 It is reported that the first CLK2 inhibitor, lorecivivint, has entered phase III clinical trials in recent years.…”
Section: Kinase Groupsmentioning
confidence: 99%
“… 95 , 96 It is reported that the first CLK2 inhibitor, lorecivivint, has entered phase III clinical trials in recent years. 94 We look forward to the therapeutic prospects of CLK2 inhibitors.…”
Section: Kinase Groupsmentioning
confidence: 99%
See 1 more Smart Citation